Answer:
x =y =
Explanation:
in order to solve this system of equation let us say
3x - 5y = -35...........................................................equation 1
12x+y=-6......................................................equation 2
from equation 2
12x+y=-6......................................................equation 2
y = -6 - 12x.......................................... equation 3
substitute for y = -6 -12x into equation 1
3x - 5y = -35...........................................................equation 1
3x -5( -6 - 12x) = -35
3x + 30 + 60x = -35
63x + 30 = -35
collect like terms
63x= -35 -30
63x = - 65
divide both sides by 63
63h/63 = -65/ 63
x = -1.03
put x = 1. 03 into equation 3
y = -6 - 12x.......................................... equation 3
y = -6 - 12( -1.03)
y = -6 + 12.38
y = 6.38